Attenuation of X and Gamma Rays in Personal Radiation Shielding Protective Clothing - Kozlovska, Michaela; Cerny, Radek; Otahal, Petr (Health physics, 2015)
A collection of personal radiation shielding protective clothing, suitable for use in case of accidents in nuclear facilities or radiological emergency situations involving radioactive agents, was gathered and tested at the Nuclear Protection Department of the National Institute for Nuclear, Chemical and Biological Protection, Czech Republic. Attenuating qualities of shielding layers in individual protective clothing were tested via spectra measurement of x and gamma rays, penetrating them. The rays originated from different radionuclide point sources, the gamma ray energies of which cover a broad energy range. The spectra were measured by handheld spectrometers, both scintillation and High Purity Germanium. Different narrow beam geometries were adjusted using a special testing bench and a set of various collimators. The main experimentally determined quantity for individual samples of personal radiation shielding protective clothing was x and gamma rays attenuation for significant energies of the spectra. The attenuation was assessed comparing net peak areas (after background subtraction) in spectra, where a tested sample was placed between the source and the detector, and corresponding net peak areas in spectra, measured without the sample. Mass attenuation coefficients, which describe attenuating qualities of shielding layers materials in individual samples, together with corresponding lead equivalents, were determined as well. Experimentally assessed mass attenuation coefficients of the samples were compared to the referred ones for individual heavy metals.
Keywords: plánování postupu v případě katastrof; Protective Clothing; Disaster Planning; dávka záření; Metals, Heavy; Photons; Radiation Protection; fotony; first responder; lidé; radiační poranění; Radiation Injuries; germanium; záření gama; X-Rays; těžké kovy; rentgenové záření; Germanium; Emergency Responders; Humans; Radiation Dosage; Software; únik radioaktivních látek; radiační ochrana; software; Radioactive Hazard Release; Gamma Rays; ochranné oděvy